Respuesta :

I hope the given equation is :

[tex] \sqrt{1-3x} =x + 3 [/tex]

First step to solve this equation to remove square root from the left side. So, take square on each sides of the equation. Therefore,

1 - 3x = (x + 3)²

1 - 3x = (x + 3)*(x + 3) Since a² = a * a

1 - 3x = x² + 3x + 3x + 3² By multiplication.

1 - 3x = x² + 6x + 9 Combine the like terms.

x² + 6x + 9 - 1 + 3x = 0 Subtract 1 and add 3x from each sides of equation

x² + 9x + 8 = 0 Combine the like terms.

Next step is to factor the trinomial to solve the above equation for x.

For that break downn the constant 8 into two multiples so that the addition of the multiples will result the coefficient of x = 9.

So, 8 = 1 * 8

Addition of 1 and 8 will give 9. So, next step is to replace 9x with 1x + 8x. So,

x² + 1x + 8x + 8 = 0

(x² + 1x) + (8x + 8) = 0 Group the terms.

x ( x + 1) + 8 (x + 1 ) = 0 Take out the common factor from each group.

(x +1 ) ( x + 8 ) = 0 Take out the common factor (x + 1).

So, x + 1 = 0 and x + 8 = 0 Set up each factor equal to 0.

Hence, x = -1 and - 8.

Next step is to plug in -1 and -8 in the original equation to cross check the solutions.

For x = -1,

[tex] \sqrt{1-3(-1)} =-1 + 3 [/tex]

[tex] \sqrt{1+3} =2 [/tex] Simplify each sides separately.

[tex] \sqrt{4} =2 [/tex]

2 = 2

2 = 2 is correct. So, x = -1 satisfy the equation.

Hence, x = -1 is the real solution of the given equation.

Similarly let's plug in x = -8 now. So,

[tex] \sqrt{1-3(-8)} =-1 + 3 [/tex]

[tex] \sqrt{1+24} =2 [/tex] Simplify each sides separately.

[tex] \sqrt{25} =2 [/tex]

5 = 2

5 = 2 is not true. So, x = -8 is the extraneous solution.

Therefore, the only solution is x = -1.

Hence, the correct choice is C.

Hope this helps you!

Answer:

It’s c if u don’t want to read all of that

Step-by-step explanation:

ACCESS MORE